2021
DOI: 10.1121/10.0003558
|View full text |Cite
|
Sign up to set email alerts
|

Modelling laser ultrasound waveforms: The effect of varying pulse duration and material properties

Abstract: Optical generation of ultrasound using nanosecond duration laser pulses has generated great interest both in industrial and biomedical applications. The availability of portable laser devices using semiconductor technology and optical fibres, as well as numerous source material types based on nanocomposites, has proliferated the applications of laser ultrasound. The nanocomposites can be deposited on the tip of optical fibres as well as planar hard and soft backing materials using various fabrication technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…However, in a recent modeling study, Rajagopal and Cox demonstrated that for longer laser pulse durations, the generated ultrasound amplitude is decreased. [74] In that sense, there is qualitative consistency with the difference in laser pulse durations used here (1064 nm: 2 ns duration; 532 nm: 10 ns). The residual ultrasound signal might be reduced further in future studies by using a laser with a shorter pulse length for photoacoustic signal generation.…”
Section: Discussionsupporting
confidence: 75%
“…However, in a recent modeling study, Rajagopal and Cox demonstrated that for longer laser pulse durations, the generated ultrasound amplitude is decreased. [74] In that sense, there is qualitative consistency with the difference in laser pulse durations used here (1064 nm: 2 ns duration; 532 nm: 10 ns). The residual ultrasound signal might be reduced further in future studies by using a laser with a shorter pulse length for photoacoustic signal generation.…”
Section: Discussionsupporting
confidence: 75%
“…The same could be achieved with a simple quarter-wave layer of an impedance-matching material like PDMS with embedded TiO [29] if the bandwidth of the generated signal could somehow be further reduced, which may be desirable depending on the detector being used. Further control over the frequency spectrum of the transducer could be achieved both by altering the laser pulse duration and by changing the physical parameters of the absorbing material [38] . In the former increasing the optical pulse duration up to values on par with the stress confinement time will broaden the generated acoustic pulse and thus decrease the bandwidth and centre frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, while the pulsed laser attenuates and heat is transmitted to other regions of the material, the thermal expansion decreases to produce vibrational displacement, namely, ultrasound [19] . The temporal characteristics of the laser pulse determine the ultrasound’s broadband bandwidth [20] , [21] . In the thermoelastic regime, the power density of the laser pulse is lower than the ablation threshold of the material, so the whole process is nondestructive.…”
Section: Methodsmentioning
confidence: 99%